Regulation of cardiovascular remodeling by the counter-regulatory axis of the renin–angiotensin system. (January 2013) - Clarke, Carolyn; Flores-Muñoz, Monica; McKinney, Clare A; Milligan, Graeme; Nicklin, Stuart A
The counter-regulatory axis of the renin–angiotensin system (RAS) is a novel therapeutic target in cardiovascular disease. Pathophysiological effects mediated via angiotensin II (Ang II) are well established in regulation of blood pressure, cardiac and vascular remodeling, and renal sodium handling, which lead to disorders such as hypertension and associated end-organ damage, atherosclerosis and heart failure. The counter-regulatory axis of the RAS is centered on the angiotensin-converting enzyme 2/angiotensin-1–7 (Ang-[1–7])/Mas receptor axis and has been shown to inhibit many detrimental phenotypes in cardiovascular disease. More recently, an alternative peptide, angiotensin-(1-9) (Ang-[1-9]), has been reported as a potential new member of this axis. This review will discuss the cardiovascular regulatory roles of Ang-(1–7) and Ang-(1–9) in the counter-regulatory axis of the RAS, and the potential for new therapeutic approaches in cardiovascular disease.